Working women in an urban setting: traders, vendors, and food security in Accra - Levin, Carol E.; Maxwell, Daniel G.; Armar-Klemesu, Margaret; Ruel, Marie T.; Morris, Saul Sutkover; Ahiadeke, Clement (International Food Policy Research Institute, 1999)
Data collected from a 1997 household survey carried out in Accra, Ghana, are used to look at the crucial role that women play as income earners and in securing access to food in urban areas. The high number of female-headed households and the large percent of working women in the sample provide a good backdrop for looking at how women earn and spend income differently than men in an urban area. Livelihood strategies for both men and women are predominantly labor based and dependent on social networks. For all households in the sample, food is still the single most important item in the total budget. Yet, important and striking differences between men and women's livelihoods and expenditure patterns exist. Compared to men, women are less likely to be employed as wage earners, and more likely to work as street food vendors or petty traders. Women earn lower incomes, but tend to allocate more of their budget to basic goods for themselves and their children, while men spend more on entertainment for themselves only. Despite lower incomes and additional demands on their time as housewives and mothers, female-headed households, petty traders, and street food vendors have the largest percentage of food secure households. This paper explores differences in income, expenditure, and consumption patterns in an effort to answer this question, and suggests ways that urban planners and policymakers can address special concerns of working women in urban areas.